Problèmes biologiques de la partie nord-ouest de la Mer Noire - Zaițev, Iuvenalie (Cercetări Marine - Recherches Marines, 2026)
New biological problems of the north-western shelf of the Black Sea are discussed based on investigations carried out in recent years. These include: the development of shipping, the building of ports, the exploitation of sand, the application of bottom trawls, discharge of industrial wastes, enforcement of the shoreline from landslides, changes in the quantitative composition of river run-off, and the influence of other kinds of man-made factors on the marine environment.